CLINICAL AND SUBCLINICAL CHARACTERISTICS ON BREAST CANCER PATIENTS TREATED WITH ANTHRACYCLINES (Vietnam Journal of Community Medicine, 2021)
Objective: Describing the clinical and subclinical characteristics on breast cancer patients treated with Anthracyclines at Thong Nhat hospital.Subjects and methods: a prospective descriptive study on 43 patients with breast cancer was treated with Anthracyclines with 4 to 6 cycles as determined by clinical doctor at Thong Nhat hospital. Results: Average age: 49.2 ± 3.2 years old. The age group accounted for the largest proportion in the study object was the 50-60 age group (48.84%). The percentage of patients who self-examined the tumor was the highest with 79.07%. There were 9.30% of patients with pain symptoms, 11.63% of patients with nipple discharge. Tumor position in the upper-external quadrant accounted for the largest percentage with 55.81%. The average size of tumors was 2.56 ± 1.2 (cm). The main form of lesions detected on ultrasound was the local lesion with over 80% with an unknown boundaryfeature (81.40%) and predominantly invasive (76.74%). The histopathological type accounted for the highest percentage was the invasive tubular carcinoma (79.07%), the medullary carcinoma andmucinous carcinoma body accounted for the lowest rate with 2.33% and 0%, respectively. The histological degree accounted for the highest percentage among the research subjects was degree 2with 50.18%. Stage III accounted for the highest rate with 46.51%.Conclusion: The most common age group for breast cancer was 50-60 years old, the main symptom was self-examination with breast tumors, breast cancer were mainly local tumor at the upper-externalposition. On ultrasound, the lesions were the local, unknown boundary, and invasive lesions. Breast cancer was mainly invasive ductal carcinoma, histologic degree 2.
Keywords: Breast cancer, Anthracycline, clinical and subclinical features